THE URBAN MUSLIM THOUGHT IN THE AGE OF INFORMATION: THE MUHAMMADIYAH’S DIGITAL QUR’ANIC INTERPRETATION - Siar Ni'mah; Amir Hamzah; Hawirah Hawirah; Umar Umar; Saifuddin Amin (Akademika : Jurnal Pemikiran Islam, 2022)
The advances in information technology change human movement in all aspects, especially urban Muslim communities. The urban Muslim communities such as the Muhammadiyah respond to the technological movements by doing the digital interpretation. This research analyzes the interpretation of the Muhammadiyah which focuses on Tafsir at-Tanwir through the Tarjih Channel of Majelis Tarjih and Tajdid PP. Muhammadiyah. The research addresses two points, namely: the method and the character of digital interpretation by Muhammadiyah presented in Tarjih Channel YouTube. This research uses the descriptive analytical Qualitative in analysing the data. The Data were collected by data condensation, reduction, presentation, and data conclusion. The results of the research show that: 1) a new form or a new media of interaction with the Qur’an in digital era, 2) the tahlily and the maudhu’i methods which are contained in presenting Tafsir at-Tanwir, and 3) the Tafsir at-Tanwir takes part in the development of contemporary interpretations, especially in the dissemination of interpretations digitally. in addition, another contribution is Muslims are now closer and easier in accessing in Qur’anic interpretation than before. These findings indicate that the urban Muslims, especially the Muhammadiyah, contribute to da'wah through the interpretation of Qur'anic verses in digital media on the tarjih channel.